Hubungan Pengetahuan dengan Kepatuhan Bidan dalam Penggunaan Partograf di Kamar Bersalin RSUD Undata Palu - Vira Pratiwi; Laura Rantalaen; Ni Made Rosiyana (Jurnal Bidan Cerdas, 2019)
Compliance in the use of partographs is one of the most important thing done by midwives to make clinical decisions, monitoring, evaluation, handling labor, early problem detection and complicated labor so that they can plan actions to overcome the problem or to give refferal the mother in the right conditions. The purpose of this study was to find out the relationship between knowledge with the compliance of midwives in the use of partographs. This study used an analytical observational design with a cross-sectional approach. The subjects in the study were all midwives who worked in the Maternity Room of Undata Palu Hospital in March-June 2018 as many as 26 respondents. Bivariate analysis used the Sperman Rank test. The results of this study were good knowledgeable midwives as many as 18 respondents (69.3%), obedient midwives as many as 16 respondents (61.5%), and the results of bivariate analysis showed that the relationship of knowledge with midwife compliance in using partograph was rs 0.529 and p-value 0.005. Conclusion: There was a relationship between knowledge and compliance of midwives in using Partographs with medium correlation strength. Suggestion: This result can be an evaluation material for respondents about the use of partograph